2017
DOI: 10.1002/ejlt.201700261
|View full text |Cite
|
Sign up to set email alerts
|

Application Of Microwaves and Megasound to Olive Paste in an Industrial Olive Oil Extraction Plant: Impact on Virgin Olive Oil Quality and Composition

Abstract: Traditional olive oil processing includes batch olive paste kneading for 30-60 min. Microwave (MW) treatment of the olive paste have recently shown to continuously provide faster conditioning, while megasound (MS) treatment have been shown to enhance oil extractability. In the present work the virgin olive oil standard parameters, sensory descriptors, and phenolic and headspace composition upon treatment of oils obtained using novel process enhancement interventions, and their combination in an industrial plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
(30 reference statements)
1
26
0
2
Order By: Relevance
“…In accordance with the previous studies concerning the recent thermal and non-thermal technologies applied to the olive oil mechanical extraction process and based on the alteration of cell membrane permeability and structure [22,26,29,30,39,40], the prototype industrial PEF model used for the treatment of Nocellara del Belice cv. olive paste did not impact values of the EVOO primary legal quality parameters, as shown in Table 2.…”
Section: Olive Oil Qualitysupporting
confidence: 72%
See 1 more Smart Citation
“…In accordance with the previous studies concerning the recent thermal and non-thermal technologies applied to the olive oil mechanical extraction process and based on the alteration of cell membrane permeability and structure [22,26,29,30,39,40], the prototype industrial PEF model used for the treatment of Nocellara del Belice cv. olive paste did not impact values of the EVOO primary legal quality parameters, as shown in Table 2.…”
Section: Olive Oil Qualitysupporting
confidence: 72%
“…Recently, different, new technologies in the olive oil extraction process have been introduced and studied to support the malaxation step with the aim of improving the oil extraction yield and final quality, such as low-frequency ultrasound [19][20][21][22], microwave [23,24], high-frequency ultrasound [25][26][27], and PEF. Andreou et al [28] used a PEF (1.6-70.0 kJ/kg) process before malaxation (30 min at 30 • C) with an extraction yield increase up to 18%.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies proposed the modification of malaxation equipment and the pretreatment or post‐treatment of the paste to improve process efficiency (Abenoza et al, ; Bejaoui et al, , ; Clodoveo, ; Clodoveo et al, ; Esposto et al, ; Fiori et al, ; Iqdiam et al, ; Leone et al, , , ; Puértolas and Martínez De Marañón, ; Sari and Ekinci, ; Tamborrino et al, ; Taticchi et al, ; Veneziani et al, , ). An approach to reduce the duration or temperature of malaxation is paste preheating using microwave (MW) treatment or high‐power ultrasound or pulsed electric field (PEF) or flash thermal treatment application or megasonic treatment (Abenoza et al, ; Clodoveo and Hachicha Hbaieb, ; Leone et al, ). Table presents an overview of the research results on the examination of premalaxation or postmalaxation treatment of the olive paste on the olive oil quality.…”
Section: Malaxationmentioning
confidence: 99%
“…The use of MW is another approach examined as a treatment of olive paste prior or instead of the malaxation process (Leone et al, , ; Tamborrino et al, ). From the available data, only one study showed an increase in the extraction yield (Leone et al, ), whereas the rest presented no effect (Leone et al, ; Tamborrino et al, ). In terms of the olive oil quality parameters, a decrease in the peroxide value was observed when MW were used in replacement of or in combination with the malaxation process and there was no effect on free acidity and K 232 , K 270 indices.…”
Section: Malaxationmentioning
confidence: 99%
See 1 more Smart Citation